The Role of Educational Management Information Systems in Supporting Decision-Making and Enhancing the Quality of Islamic Educational Institutions: A Literature Review - Rahmaliawati Rahmaliawati; Eka Putri; Eliyana Fitri; Rosdaini Rosdaini; Sri Atika; Alpiza Zahra; Rianda Prastiya (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2026)
The development of information technology has brought significant changes in the management of educational institutions, including Islamic educational institutions. This study analyzes the role of Educational Management Information Systems (EMIS) in supporting decision-making and enhancing the quality of Islamic educational institutions through a literature review approach. This study uses a library research method, examining scientific articles, books, and academic documents published within the last ten years. Data were collected through searches on various academic databases and analyzed using content analysis techniques, which include identification, classification, evaluation, and synthesis of research findings. The results of the study show that EMIS serves as a strategic information source that provides accurate, integrated, and real time data to support data-driven decision making. The use of EMIS helps Islamic educational institutions plan, implement, monitor, and evaluate educational programs more effectively, objectively, and accountably, while contributing to institutional quality through the optimization of academic, personnel, financial, facilities and infrastructure, and student service management. The effectiveness of EMIS implementation is influenced by data quality, human resource competence, leadership support, organizational culture, availability of technological infrastructure, and system integration. Unlike previous studies that discuss EMIS's role in decision-making or quality improvement separately, this study integrates both aspects specifically within Islamic educational institutions, an area still relatively underexplored. Therefore, optimizing EMIS requires strengthening data governance, improving digital literacy, and organizational commitment to building a data-driven decision-making culture. This study confirms that EMIS is a strategic instrument for sustainably improving the governance and quality of Islamic educational institutions.